Hydroxycarboxylic acid receptor 2 (HCA2) agonists induce NET formation and MMP-9 release from bovine polymorphonuclear leukocytes. (February 2023) - Carretta, Maria Daniella; Creutzburg, Paz; Borquez, Katherine; Quiroga, John; Alarcón, Pablo; Rivera, Andrés; Burgos, Rafael Agustin
Abstract: Periparturient cows are commonly fed diets supplemented with Niacin (nicotinic acid, NA) because of its anti-lipolytic properties. NA confers its anti-lipolytic effects by activating the hydroxycarboxylic acid 2 receptor (HCA2). HCA2 is also activated by the ketone body beta-hydroxybutyrate (BHB) and circulating BHB levels are elevated in postpartum dairy cows. The HCA2 receptor is highly expressed in bovine polymorphonuclear leukocytes (PMN) and could link metabolic and innate immune responses in cattle. We investigated how HCA2 agonists affected bovine PMN function in vitro . We studied different PMN responses, such as granule release, surface expression of CD11b and CD47, generation of neutrophil extracellular traps (NETs), and apoptosis. NA, BHB, and 4, 4aR, 5, 5aR-tetrahydro-1H-cyclopropa [4, 5] cyclopenta [1, 2-c] pyrazole-3-carboxylic acid (MK-1903) treatment triggered the release of matrix metalloproteinase 9 (MMP-9), a component of the tertiary granule, from neutrophils. Additionally, all HCA2 agonists induced NETs formation but did not affect surface expression of CD11b and CD47. Finally, none of the HCA2 agonists triggered apoptosis in bovine PMN. This information will give new insights into the potential role of the HCA2 receptor in the bovine innate immune response. Graphical abstract: Image 1 Highlights: Ligands of HCA2 receptor, including beta-hydroxybutyrate, nicotinic acid and MK-1903, induce NETs formation in bovine PMN. Nicotinic acid and MK-1903 induce metalloproteinase 9 release in bovine PMN. HCA2 receptor agonists do not affect CD11b or CD47 expression or apoptosis in bovine PMN.